Flutter Speed Limits of Cantilever Rectangular and Tapered Plates - Jabir, Kusay H. (Al-Khwarizmi Engineering Journal, 2007)
The aerodynamic and elastic forces may cause an oscillation of the structure such as the high frequency of the airfoil surfaces and the dynamic instability occurring in an aircraft in flight and failure may occur at a speed called flutter speed. In this work, analytical and numerical investigations of flutter limits of thin plates have been carried out. The flutter speed of rectangular plates were obtained and compared with some published results. Different design parameters were investigated such as aspect ratio, thickness and their effects on flutter velocity. It was found that the structural mode shape plays an important role in the determination of the flutter speed and the coupling between the bending and torsional mode is the main cause of flutter.